Successful endoscopic treatment of a huge trichobezoar in a 10‐year‐old girl - Ko Matsuura; Shoji Oura; Kohei Ishibashi; Yoichi Matsumoto; Wataru Ono (DEN Open)
Abstract A 10‐year‐old girl was admitted to our hospital due to acute pancreatitis. Computed tomography showed an intra‐gastric mass containing multiple small air bubbles. Ultrasound showed a well‐circumscribed large oval mass with a broad acoustic shadow. Endoscopy revealed a huge trichobezoar with many movable hairs, being judged by the cause of acute pancreatitis. Due to the parents’ strong preference not to leave any surgical scars on their daughter, the patient underwent endoscopic treatment. The trichobezoar grasped with a snare was too large to pass through the esophageal‐gastric junction. In addition, the outer layer of the trichobezoar was too hard to be cut with conventional endoscopic devices but was successfully cut with a FlushKnife. The content of the trichobezoar was much softer than its hard surface but needed appropriate counter‐traction to be torn off the tissue. Two alligator forceps via a dual‐channel multi‐bending scope were able to give sufficient counter‐traction to the inner tissue of the trichobezoar, successfully removing the trichobezoar through piece‐by‐piece tearing off. All the endoscopic procedures took seven hours for the complete trichobezoar removal. The total weight of the dissected mass was 180 g. The girl resumed eating on the next day and was discharged on the third day. Physicians should note that a medical team with full endoscopic expertise can remove huge trichobezoars using a FlushKnife, a dual‐channel multi‐bending scope, and two alligator forcepses.